MESIN AYAKAN GETAR TIPE EXCENTRIC SEBAGAI PENGAYAK BUTIRAN MARMER DAN BATU ALAM PADA PRODUKSI INDUSTRI TERASO DARI LIMBAH BATU ALAM DI KABUPATEN TULUNGAGUNG - Aditya, Candra; Silviana, '; Hermawati, Adya (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2018)
The terrazzo industry is an industry that has long been developing. Although it was sunk by the rise of ceramic materials, but recently terrazzo began to rise again. Its products are developing not only as floor coverings but also as wall coverings, kitchen tables, sinks and bathtubs. CV. Sari Hutan in Campurdarat Subdistrict, Tulungagung Regency, produces terrazzo raw materials from natural stones, namely marble, onyx and siolite. This business produces various types of terrazzo with the main raw material from natural stone waste. This industry is unique because not many have this kind of business and the product has a large export potential. This is based on the products produced by consumers both domestically and abroad, including France. Consumer interest in this product because it has exclusivity is the embodiment of a product that is customized and stylish. From the results of the situation analysis, it was found that the most urgent problem was the production capacity of SMEs that had not been optimal in meeting market demand. This is related to production support tools that are still not efficient. The process of grinding and sifting natural stones to produce broken marble, natural stone as the main raw material for terrazzo has not been optimal. The solution is to make production support tools more effective and efficient to produce more quality terrazzo. The main work of this activity is to produce a three-level excentric type vibrating screen, which is an automatic sieve used for the process of sifting marble granules, natural stones that are more effective and efficient. The results of engine efficiency calculation are vibrating screen excentric type Compared to the previous machine in terms of production capacity, electricity costs, the size of the grain produced, the terazo material produced has an average efficiency of 150%.